2019
DOI: 10.1002/jsfa.9674
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of scoparone from chestnut inner shell on platelet‐derived growth factor‐BB‐induced vascular smooth muscle cell migration and vascular neointima hyperplasia

Abstract: BACKGROUND: Compounds of the inner shell of chestnut (Castanea crenata) have diverse biological activities, including anti-cancer and anti-oxidant activities. Here we explored the effects of an extract of chestnut inner shells and of its bioactive component scoparone on vascular smooth muscle cell migration and vessel damage. RESULTS:The ethanol extract of chestnut inner shells, containing 11 major compounds, inhibited platelet-derived growth factor (PDGF)-BB-induced migration of rat aortic smooth muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Phenolic compounds in CIS also inhibited the migration of rat aortic smooth muscle cells (RASMC) induced by platelet-derived growth factor (PDGF) BB. In particular, scoparone in CIS inhibited RASMC cell migration and wound healing under PDGF-BB, but did not affect RASMC proliferation (Jung et al, 2019). This revealed the potential application of CIS as a new functional food and drug to prevent restenosis and atherosclerosis.…”
Section: Other Health Effects Of Chestnut Shellsmentioning
confidence: 90%
“…Phenolic compounds in CIS also inhibited the migration of rat aortic smooth muscle cells (RASMC) induced by platelet-derived growth factor (PDGF) BB. In particular, scoparone in CIS inhibited RASMC cell migration and wound healing under PDGF-BB, but did not affect RASMC proliferation (Jung et al, 2019). This revealed the potential application of CIS as a new functional food and drug to prevent restenosis and atherosclerosis.…”
Section: Other Health Effects Of Chestnut Shellsmentioning
confidence: 90%
“…However, other scholars declared that transplanting EPCs could not only promote reendothelialization through paracrine modes of action, but also differentiate into mature ECs [40,41]. Assessment of transplanted EPCs and reendothelialization requires sequential crossor longitudinal sectioning of the vessels [42][43][44][45], but not every section could be chosen to stain and quantify [46][47][48]. The irregular geometry of the cell distribution requires accurate tools.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that scoparone can mitigate cardiac ischemia/reperfusion injury in in vitro and in vivo settings ( 129 ). Scoparone also has anti-atherogenic effects including the inhibition of vascular smooth muscle cell proliferation and migration ( 130 , 131 ), inhibition of platelet aggregation ( 132 ), and the attenuation of atherosclerotic plaque formation and dyslipidemia in hyperlipidemic diabetic rabbits ( 133 , 134 ). One study also found that scoparone decreased peroxisome proliferator-activated receptor gamma (PPARγ) activity, expression of PPARγ target genes, and lipid accumulation in differentiating 3T3-L1 adipocytes ( 135 ).…”
Section: Effects Of Bioactive Compounds Found In a Scopariamentioning
confidence: 99%